Situation Report: Hungary, 12 November 1974 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Some Statistics on Hungarian Trade Union Membership Soccer Scandal Exposed Decree - Law on State and Public Security Problems in the First Six Months of 1974 Chemical Supply Problem in Agriculture